PENYELIDIKAN LETAK AKUMULASI LINDI DAN ARAH REMBESAN DENGAN MENGGUNAKAN KONFIGURASI WENNER-SCHLUMBERGER DI TPAS AMPANG KUALO KOTA SOLOK - Yoszi Mingsi Anaperta; Fitra Rifwan; Andree Octova (Jurnal Teknologi Informasi dan Pendidikan, 2017)
TPAS Ampang Kualo is a final waste dumping area in Kota Solok of Sumatera Barat. The research at TPAS Ampang Kualo aims to know the distribution of leachate. Geolistrik resistivity method by Wenner - Schlumberger configuration is used for data retrieval Resistivity meter MAE X612 EM. The measurement data is then converted by using Res2dinv software to generate 2D resistivity profile and Voxler 4.0 software for 3D resistivity profile. The results show that leachate seepage at TPAS Ampang Kualo on track one was around a leachate pond stretching from South to North. The leachate was detected at depths between of 2.10 to 5.80 meters. In track two, the presence of leachate was indicated around a leachate pond stretching from east to west. It was detected at depths beetween of 1.50 to 6.35 meters. The trajectory three was taken around the residential population stretching from South to North that cuts out the flow of the leachate ditch. The leachate was detected at a depth of 0.25 to 7.38 meters. It was concluded that the distribution of TPAS Ampang Kualo leachate spread from the South to the Southwest was down in a small ditch flow for leachate disposal that ending at Green Hills Arya Residen. Keywords: TPAS Ampang Kualo, Leachate, Geolistrik Resistivity Method, Wenner-Schlumberger Configuration